PASAR LAYAR BERBASIS E-COMMERCE - Rewindy Astari Surbakti; Doddy Yuono (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The 21st century is known as the industrial revolution 4.0 which changes the economy among people who grow together with modernity and technology systems. It proves that the development of human thinking on creativity will greatly affect the development of the creative economy, but this has made the market begin to be abandoned by new generations and switch to e-commerce systems. The existence of an epidemic that has begun to spread in people's lives is also one of the factors that have changed the world economy and made the market begin to be abandoned. Changes in the world economy will require revitalization so that this is used as a foundation in the formation of the Screen Market integrated with the digital system to polarize the economy. The new generation is the key to the development and balance of the economy in technology, this is in line with the entrepreneurial nature and character of the new generation, which makes them prefer to develop as start ups. The revitalization of the economic center will become a forum for interaction with the surrounding environment so that the characteristics of the formation of interaction space are the basis and the beginning of the screen market. The screen market is located on Jl Arjuna Utara which is surrounded by malls, offices, universities, making the type of retail being marketed a creative sub-sector, namely culinary with local products, fashion retail, and also craft retail managed by start ups so it is hoped that the screen market can accommodate interaction and creatively combined with digital developments. Keywords: Economy; Market; New Generation; Technology. Abstrak Abad ke-21 dikenal dengan terjadinya revolusi industri 4.0 yang mengubah  perekonomian  di kalangan masyarakat yang bertumbuh bersama dengan sistem modernitas dan juga teknologi. Membuktikan bahwa perkembangan pemikiran manusia terhadap kreativitas akan sangat memengaruhi perkembangan ekonomi kreatif tetapi hal ini menjadikan pasar mulai ditinggalkan oleh generasi baru dan beralih pada sistem e-commerce. Adanya wabah yang mulai merambat dikehidupan masyarakat juga menjadi salah satu faktor yang merubah perekonomian dunia dan menjadikan pasar mulai ditinggalkan. Perubahan perekonomian dunia ini akan membutuhkan revitalisasi sehingga hal ini dijadikan sebagai landasan pijakan dalam pembentukan Pasar Layar yang dipadukan dengan sistem dari digital sebagai polarisasi perekonomian. Generasi baru merupakan kunci dari perkembangan dan keseimbangan perekonomian dalam teknologi, hal ini sejalan dengan sifat dan watak entrepreneur yang dimiliki oleh generasi baru sehingga menjadikan mereka lebih memilih berkembang sebagai start up. Revitalisasi pusat perekonomian ini akan menjadi wadah interaksi dengan lingkungan sekitar sehingga adanya karakteristik pembentukan ruang interaksi sebagai dasar dan awal dalam pasar layar. Pasar layar berada di Jl. Arjuna Utara yang dikelilingi oleh mall, kantor, universitas menjadikan jenis retail yang dipasarkan merupakan subsektor kreatif yaitu kuliner dengan produk lokal, retail fashion dan juga retail kriya yang dikelola start up sehingga diharapkan Pasar Layar mampu menampung antara interaksi dan kreatif  yang dipadukan dengan perkembangan digital.